2001
DOI: 10.1037/0021-9010.86.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in utilizing control to cope with job demands: Effects on susceptibility to infectious disease.

Abstract: This study examined the interactive effects of job demands, control, and individual characteristics on upper respiratory illnesses and immune function. Having high job control appeared to lessen the linkage between job demands and poor health among individuals with high self-efficacy and those who perceived that they were not often responsible for negative job outcomes. Conversely, having high job control exacerbated the association between job demands and poor health among inefficacious individuals. Implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 43 publications
6
84
1
3
Order By: Relevance
“…As for locus of control, however, there are discrepancies in these findings. Schaubroeck and colleagues demonstrated that job control is beneficial under conditions of high demands only for employees with high job related self-efficacy, the dependent variables being blood pressure (Schaubroeck & Merritt, 1997) and chronic symptoms of upper respiratory infections (Schaubroeck et al, 2001). Similarly, in a longitudinal study by Jimmieson (2000), high job control buffered the effect of role conflict on depersonalization only among individuals with high job selfefficacy.…”
Section: Self-efficacy and The Stressor-control Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for locus of control, however, there are discrepancies in these findings. Schaubroeck and colleagues demonstrated that job control is beneficial under conditions of high demands only for employees with high job related self-efficacy, the dependent variables being blood pressure (Schaubroeck & Merritt, 1997) and chronic symptoms of upper respiratory infections (Schaubroeck et al, 2001). Similarly, in a longitudinal study by Jimmieson (2000), high job control buffered the effect of role conflict on depersonalization only among individuals with high job selfefficacy.…”
Section: Self-efficacy and The Stressor-control Interactionmentioning
confidence: 99%
“…Two of the dispositional characteristics that have been studied frequently in the context of the JDC model are locus of control and self-efficacy (e.g., Schaubroeck et al, 2001;Rodriguez et al, 1999). Although people with a tendency toward an internal locus of control (referred to as "internals" below) believe that most outcomes are the result of their own actions, people who tend towards an external locus of control ("externals") believe that external sources (chance, other persons) determine their outcomes (Rotter, 1966).…”
mentioning
confidence: 99%
“…Individuals who believe that they have the resources and capacity to cope with the demands they encounter may be said to have positive self-efficacy expectations (Hobfoll & Shirom, 2001). Schaubroeck, Jones, and Xie (2001) argue that only those with high self-efficacy "fit" into Karasek's (1979) demands-control model, while those lacking self-efficacy do not. For example, Schaubroeck and colleagues (2001) found that individuals with high self-efficacy who experience high control show more favorable health, whereas individuals with low self-efficacy who experience high control show a stronger association between high work demands and poor health.…”
Section: Work Stress and Personalitymentioning
confidence: 99%
“…One moderator that has received consistent support in the JDC model is self-efficacy. Support for the demand-control model was found when employees perceived a good fit or had high self-efficacy however for those with low selfefficacy increased control may actually increase negative outcomes (Jimmieson, 2000;Schaubroeck, Jones & Xie, 2001;Schaubroeck & Merritt, 1997).…”
Section: Self-efficacy As a Moderatormentioning
confidence: 99%
“…This is a 10-item scale designed to tap individual selfefficacy regarding job-related performance without specifying work tasks. Responses are given on a six-point Likert-type scale in which the anchors are very inaccurate and very accurate (Schaubroeck et al, 2001). In a previous study of 217 full-time employees of a research organization the coefficient alpha was 0.74 (Schaubroeck et al).…”
Section: Self-efficacymentioning
confidence: 99%